2022
DOI: 10.22541/au.164865114.40514314/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of high frequency oscillatory ventilation combined with pulmonary surfactant in the treatment of acute respiratory distress syndrome after cardiac surgery: a prospective randomized controlled trial

Abstract: Objective: This study aimed to evaluate the effects of pulmonary surfactant (PS) combined with high-frequency oscillatory ventilation (HFOV) or conventional mechanical ventilation (CMV) in infants with acute respiratory distress syndrome (ARDS) after congenital cardiac surgery. Method: A total of 61 infants with ARDS were eligible and were randomized to the CMV + PS group (n= 30) or the HFOV + PS group (n= 31) between January 2020 and December 2020. The primary outcomes were the improvement of the arterial blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Moreover, some studies have suggested that the use of a humidifier may be effective if a patient exhibits viscous sputum (39). Lateral position ventilation combined with vibration sputum drainage is more effective in promoting expectoration and improving respiratory function (40). Wirén et al (41) reported that patients with respiratory disease symptoms had an increased risk of hypoxaemia following surgery.…”
Section: Risk Factors For Postoperative Hypoxaemiamentioning
confidence: 99%
“…Moreover, some studies have suggested that the use of a humidifier may be effective if a patient exhibits viscous sputum (39). Lateral position ventilation combined with vibration sputum drainage is more effective in promoting expectoration and improving respiratory function (40). Wirén et al (41) reported that patients with respiratory disease symptoms had an increased risk of hypoxaemia following surgery.…”
Section: Risk Factors For Postoperative Hypoxaemiamentioning
confidence: 99%